Gestión del espectro radioeléctrico en Colombia - Ernesto Cadena Muñoz; Hermes Javier Eslava Blanco; José Alejandro Franco Calderón (Tecnura, 2015)
This paper shows a survey of radio spectrum management, defines some basic concepts that allow recognizing its scope and importance for the sector and an analysis of different spectrum management model sigh lighting features, strengths and weaknesses of each for its application. It analyzes the context of the country where it is observed that the traditional management model used is not efficient, generating economic losses for the country in one of the most important resources on Telecommunications, which leads us to reconsider the current model of radio spectrum management in Colombia. Finally, it’s presented the trends in spectrum management and highlights the need for analysis of the model based on the telecommunications market, the requirements for its implementation in the country and the difficulties that it can find.